Cigarette smoking and risk of celiac disease: A systematic review and meta-analysis. Issue 9 (November 2018) - Wijarnpreecha, Karn; Lou, Susan; Panjawatanan, Panadeekarn; Cheungpasitporn, Wisit; Pungpapong, Surakit; Lukens, Frank J.; Ungprasert, Patompong
Background/Objectives: A negative association between cigarette smoking and celiac disease has been observed but results were inconsistent across the published studies. A meta-analysis was conducted with the aim to identify all studies that investigated this association and to summarize the results of those studies. Methods: A comprehensive literature review was conducted utilizing MEDLINE and Embase databases through March 2018 to identify all cohort studies and case-control studies that compared the risk of celiac disease among current and/or former smokers versus never-smokers. Effect estimates from each study were extracted and combined together using the random-effect, generic inverse variance method of DerSimonian and Laird. Results: A total of seven studies with 307, 924 participants fulfilled the eligibility criteria and were included in the meta-analysis. The pooled analysis found a significantly decreased risk of celiac disease among current smokers compared with never-smokers with the pooled odds ratio (OR) of 0.52 (95% confidence interval (CI), 0.32–0.84; I 2 86%). However, the risk of celiac disease among former smokers was not significantly different from never-smokers with the pooled OR of 1.10 (95% CI, 0.76–1.60; I 2 of 73%). Conclusions: A significantly decreased risk of celiac disease among current smokers compared with never-smokers was demonstrated in this meta-analysis.